(untitled) (Journal of Energy and Safety Technology (JEST), 2025)
This study addresses the need for safer, more hygienic, and energy-efficient control of electrical loads in residential, healthcare, and industrial environments by developing a multi-switching contactless system. Conventional single-mode switching systems are limited by network dependency, restricted range, and inconsistent reliability, creating a demand for a multi-switching solution that ensures redundancy and responsive operation. The proposed system integrates an Arduino Uno as the central controller, a 433 MHz RF sensor for local wireless control, an ESP-32 Wi-Fi module for remote management, and a 5V relay module to switch multiple electrical loads. Users can operate the system via a mobile application or an RF remote, providing flexible and contactless interaction. The development involved hardware assembly, Arduino and ESP-32 firmware programming, mobile app integration, and structured testing including unit, integration, and functional evaluations to ensure performance and reliability. Experimental results demonstrated mean response times of 118 ms for RF and 176 ms for Wi-Fi control, an RF open-space range of up to 98 meters, command execution success rates of 98.5% (RF) and 97.1% (Wi-Fi), and safe load handling up to 1200 W with relay temperatures remaining below 48°C. These findings confirm that the system operates reliably under diverse conditions while maintaining low latency and thermal safety. In conclusion, the multi-switching contactless system offers a scalable, dependable, and practical solution for smart automation, enhancing hygiene, convenience, and energy management, with potential for future enhancements including voice control, improved security, and expanded load capacity.